1992
DOI: 10.1113/jphysiol.1992.sp019154
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic inhibitory effects of the peptides NPY, PYY and PP on nicotinic EPSPs in guinea‐pig gastric myenteric neurones.

Abstract: SUMMARY1. Neuropeptide Y (NPY), peptide YY (PYY) and pancreatic polypeptide (PP) affect gastrointestinal effector systems. Although their precise mode of action is unknown it is suggested that their effects are partly mediated by enteric neurones. Therefore, the aim of this study was to investigate the effects of NPY, PYY, avian PP (aPP) and bovine PP (bPP) on the electrophysiological behaviour of gastric myenteric neurones using intracellular recording methods.2. In all thirty-one neurones tested, electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In agreement, nitric oxide evoked a presynaptic reduction of excitatory input to myenteric neurons, although this has been attributed mainly to inhibition of peptidergic synapses (Tamura et al, 1993). In the stomach, it has been shown that neuropeptide Y acted presynaptically to reduce cholinergic fast EPSPs, which would result in reduced release of acetylcholine (Schemann and Tamura, 1991). Because most nitrergic neurons in the stomach were neuropeptide Y-immunoreactive , this peptide might also be involved in the 5-OHI P-induced decrease of the stimulusevoked contractions.…”
Section: Functional Aspect Of 5-ht-mediated Responses: Role Of 5-ht Imentioning
confidence: 59%
“…In agreement, nitric oxide evoked a presynaptic reduction of excitatory input to myenteric neurons, although this has been attributed mainly to inhibition of peptidergic synapses (Tamura et al, 1993). In the stomach, it has been shown that neuropeptide Y acted presynaptically to reduce cholinergic fast EPSPs, which would result in reduced release of acetylcholine (Schemann and Tamura, 1991). Because most nitrergic neurons in the stomach were neuropeptide Y-immunoreactive , this peptide might also be involved in the 5-OHI P-induced decrease of the stimulusevoked contractions.…”
Section: Functional Aspect Of 5-ht-mediated Responses: Role Of 5-ht Imentioning
confidence: 59%
“…As PYY3-36 readily crosses the blood–brain barrier 146 , an effect on neurons of the DMV is probable; in fact, brainstem microinjections of PYY induce either excitation or inhib ition of gastric motility, depending on the basal activity of the stomach 147151 . Electrophysiological recordings confirm a Y2 receptor-mediated response of PYY on identified vagal motor neurons 84,86 as well as on enteric neurocircuits 152 . The mechanism of action of PYY on vagal motor neurons varied in concert with brainstem levels of cAMP 84 , suggesting a means to explain the puzzling opposing responses (either excitation or inhibition of gastric motility) observed in the in vivo experiments on gastric motility 147,148 .…”
Section: Gastrointestinal Peptidesmentioning
confidence: 65%
“…Because NPY is capable of exerting profound effects, both facilitatory and inhibitory, on ganglionic transmission in enteric neurons (Schemann and Tamura, 1992;Zafirov et al, 1992;Cunningham et al, 1994a,b;Browning et al, 1996;Hirai et al, 1997), the effects of this previously unknown, nonnoradrenergic, sympathetic innervation by NPY-containing nerves on colonic motility and secretion merit investigation.…”
Section: Discussionmentioning
confidence: 98%